2023
DOI: 10.1108/gm-03-2022-0085
|View full text |Cite
|
Sign up to set email alerts
|

Burnout effect on working mothers in leadership positions during the COVID-19 lockdown

Yvette Mucharraz y Cano,
Diana Davila Ruiz,
Karla Cuilty Esquivel

Abstract: Purpose This study aims to understand how the recent COVID-19 pandemic impacted burnout levels among working mothers in leadership positions and how income and work schemes play an important role in their burnout. Design/methodology/approach Data were collected from 961 working mothers and fathers in leadership positions in Mexico under different work schemes during the COVID-19 lockdown. Snowball sampling was used in this study. The Maslach Burnout Inventory General Survey was distributed online, using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The topic of gender and leadership was also highlighted. According to a study, female CEOs who are also moms may be more prone to burnout [98]. It has been discovered that mixed work arrangements, which include office and homework, lessen the likelihood of burnout.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The topic of gender and leadership was also highlighted. According to a study, female CEOs who are also moms may be more prone to burnout [98]. It has been discovered that mixed work arrangements, which include office and homework, lessen the likelihood of burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Mucharraz y Cano et al [98] studied the gender aspect of working executives in Mexico and found that burnout was more common in female executives who are mothers than in male executives. A mixed work organization, i.e., working from home and office, reduced burnout tendencies.…”
Section: Challenges Faced By Leaders In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, it was observed that women were juggling between family and work-related responsibilities (Greenhaus and Beutell, 1985; Gregory and Milner, 2009; Mucharraz y Cano et al , 2023), whereas men were observed to be preoccupied with work, with less time being devoted to family (Nyman and Pettersson, 2002). Therefore, the organization’s employee benefit policies focused on working women, which aimed to decrease the role-strain arising from their work–family conflict (Mucharraz y Cano et al , 2023). However, gradually, men realized their responsibilities toward their homes and children (Galinsky et al , 2009).…”
Section: Literature Reviewmentioning
confidence: 99%